Peroxisome-mitochondria interplay and disease - Schrader, Michael; Islinger, Markus (Journal of inherited metabolic disease, 2015)
Peroxisomes and mitochondria are ubiquitous, highly dynamic organelles with an oxidative type of metabolism in eukaryotic cells. Over the years, substantial evidence has been provided that peroxisomes and mitochondria exhibit a close functional interplay which impacts on human health and development. The so-called “peroxisome-mitochondria connection” includes metabolic cooperation in the degradation of fatty acids, a redox-sensitive relationship, an overlap in key components of the membrane fission machineries and cooperation in anti-viral signalling and defence. Furthermore, combined peroxisome-mitochondria disorders with defects in organelle division have been revealed. In this review, we present the latest progress in the emerging field of peroxisomal and mitochondrial interplay in mammals with a particular emphasis on cooperative fatty acid β-oxidation, redox interplay, organelle dynamics, cooperation in anti-viral signalling and the resulting implications for disease.